2011
DOI: 10.1097/tp.0b013e31822057f1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Everolimus Introduction on Cardiac Allograft Vasculopathy—Results of a Randomized, Multicenter Trial

Abstract: Conversion to everolimus and reduced CNI does not influence CAV progression among maintenance HTx recipients. However, background immunosuppressive therapy is important as AZA+everolimus patients demonstrated attenuated CAV progression and a decline in inflammatory markers, whereas the opposite pattern was seen with everolimus+MMF. The different effect of everolimus when combined with AZA versus MMF could potentially reflect hitherto unknown interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 23 publications
5
54
3
1
Order By: Relevance
“…For these reasons, many trials use IVUS as the gold standard to assess the effect of drug treatments on CAV. 24,25 Despite this, the added value over angiography alone for routine clinical use remains uncertain. 26 In children, there are technical limitations, and it remains an invasive technique usually requiring sedation or anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, many trials use IVUS as the gold standard to assess the effect of drug treatments on CAV. 24,25 Despite this, the added value over angiography alone for routine clinical use remains uncertain. 26 In children, there are technical limitations, and it remains an invasive technique usually requiring sedation or anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies showed a significant antiproliferation potential of this medication regarding CAV mitigation and deceleration and hence improved long-term mortality after HTx (ref. [20][21][22][23][24] ). Statins represent another medication which can positively influence CAV.…”
Section: Discussionmentioning
confidence: 99%
“…Drug monitoring is done by HPLC coupled with mass spectrometry and an immunoassay is being developed. EvE showed to have antiproliferative effects delaying the onset of cardiac transplant vasculopathy and reducing the rate of CMV infections [77,81]; it is increasingly used, up to 2.6 % in HTx recipients in the years 2008 and 2009 [12]. Due to the favourable effects it may be used in children and is currently investigated (RAD 2313).…”
Section: Everolimusmentioning
confidence: 99%